Формування основ самовладання у дітей 5-6 років - Згода, Вікторія Валентинівна (My University, 2023)
Магістерська робота «Формування основ самовладання у дітей 5-6 років» досліджувалася на теоретичному й емпіричному рівнях. На теоретичному рівні обґрунтована проблема розвитку основ самовладання старших дошкільників у контексті вольового розвитку, зокрема: проаналізовано стан дослідження питання самовладання у наукових дослідженнях; здійснено огляд та відповідну аналітичну роботу над питанням чинників розвитку основ самовладання у дітей 5–6 років Для розв’язання емпіричних завдань дослідження, створені програма та методика констатувального експерименту, уточнені компоненти, розроблені критерії та показники основ самовладання старших дошкільників та схарактеризовані його рівні, на основі яких були обґрунтовані педагогічні умови та розроблено систему роботи щодо оптимізації процесу виховання основ самовладання старших дошкільників в умовах ЗДО.
The master's thesis "Formation of the Basics of Self-Control in Children of 5-6 Years of Age" was researched at the theoretical and empirical levels. At the theoretical level, the problem of developing the foundations of self-control of senior preschoolers in the context of volitional development is substantiated, in particular: the state of research on self-control in scientific research is analyzed; a review and relevant analytical work on the factors of development of self-control in children aged 5-6 years is carried out To solve the empirical tasks of the study, the program and methodology of the ascertaining experiment were created, the components were clarified, criteria and indicators of the foundations of self-control of senior preschoolers were developed and its levels were characterized, on the basis of which the pedagogical conditions were substantiated and a system of work was developed to optimize the process of educating the foundations of self-control of senior preschoolers in the conditions of preschool educational institutions. Keywords: self-control, volitional development, volitional behavior of senior preschoolers, discipline, basics of self-control of senior preschoolers.
Keywords: самовладання; вольовий розвиток; вольова поведінка старших дошкільників; дисциплінованість; основи самовладання старших дошкільників